Machine For Preparing the Soil for Sowing Melons Under the Film (Texas Journal of Multidisciplinary Studies, 2021)
The aim of the study is to develop a machine for preparing the soil for sowing melons under a tunnel film. The authors have developed a machine for preparing the soil for sowing melons under a tunnel film, which is equipped with deep-diggers with an inclined stand of the "paraglaw" type, a furrow maker and rotary working bodies. A design diagram and a fragment of the machine operation are given. The basic principles and methods of classical mechanics, mathematical analysis and statistics were used in this study. Tests have established that the developed machine reliably performs the specified technological process and its performance indicators fully meet the requirements. When using the developed machine for preparing the soil for sowing melons under the film, the direct cost of processing one hectare of area is reduced by 33.4%.